Analysis of economic indicators in scope of consumer lending - Кац, Дар’я Павлівна; Сердюк, Любов Василівна (Eastern-European Journal of Enterprise Technologies, 2011)
The article analyzes the impact of economic indicators in consumer credit and proposed approaches to productive credit policy and effective risk management